2020
DOI: 10.3390/nano10040701
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Wave Laser-Induced Transfer of Metal Nanoparticles to Arbitrary Polymer Substrates

Abstract: Laser-induced forward transfer (LIFT) and selective laser sintering (SLS) are two distinct laser processes that can be applied to metal nanoparticle (NP) ink for the fabrication of a conductive layer on various substrates. A pulsed laser and a continuous-wave (CW) laser are utilized respectively in the conventional LIFT and SLS processes; however, in this study, CW laser-induced transfer of the metal NP is proposed to achieve simultaneous sintering and transfer of the metal NP to a wide range of polymer substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…As a consequence, different experimental configurations including capillary-assisted [ 83 ] and shear-assisted [ 42 , 84 ] laser direct writing have been proposed to overcome such limitation. It is further confirmed that a similar scheme is compatible with a wider polymer substrates [ 85 ]. On the other hand, NP can be selectively transferred from the donor substrate to the acceptor substrate using a pulsed laser [ 86 , 87 , 88 ], which is applicable even to arbitrary 3D structures [ 89 ].…”
Section: Experimental Schemesmentioning
confidence: 53%
“…As a consequence, different experimental configurations including capillary-assisted [ 83 ] and shear-assisted [ 42 , 84 ] laser direct writing have been proposed to overcome such limitation. It is further confirmed that a similar scheme is compatible with a wider polymer substrates [ 85 ]. On the other hand, NP can be selectively transferred from the donor substrate to the acceptor substrate using a pulsed laser [ 86 , 87 , 88 ], which is applicable even to arbitrary 3D structures [ 89 ].…”
Section: Experimental Schemesmentioning
confidence: 53%
“…Good pulse to pulse stability guarantees reproducibility of the printed outcomes. With the aim to reduce costs, continuous wave (CW) lasers have also been demonstrated able to print conductive inks by LIFT [25][26][27]. In general, the laser wavelength does not play a key role in the process.…”
Section: Methodsmentioning
confidence: 99%
“…To address this issue, nowadays, a new technique called microscale AM is being employed to fabricate parts at the micro-and nanoscales. The DW process is a widely used AM technology for such microfabrication of conductive micropatterns using Ag, Au and Cu metals [150,151]. Among these, Cu is considered to be the key material for low-cost printing [152].…”
Section: Femtosecond Laser Sintering Of Coppermentioning
confidence: 99%
“…This can be facilitated by using AM technologies, such as SLS, that can process metal NPs and also in direct writing technology. Initially, the SLS process was used for NPs of noble metals like silver and gold, but later it was also expanded to more cost-effective materials such as copper and nickel [151]. Silver material has been utilised by inkjet technology-based AM process for fabrication of temperature sensors [168][169][170].…”
Section: Femtosecond Laser Sintering Of Silvermentioning
confidence: 99%